Alkotmányozási eljárások Magyarországon (1989-2011) - Balogh, Éva (Debreceni Jogi Műhely, 2014)
In my research paper I study the Hungarian constitutional processes. The subjects of my analysis are three periods, namely the change of the political system in 1989, the constitutional attempts from 1994 to 1998, and the constitutional process between 2010 and 2011. The processes are examined on the basis of the two notions: “legality” and “legitimacy”. Under the concept “formal legality”, I mean the legal validity of the constitutional process; i.e. whether the constitutional process takes place in accordance with the current legislation. The concept of “legitimacy” has two aspects. On the one hand, empirical legitimacy investigates whether the citizens de facto accept the constitution and value it as respectable independently of the normative motives of its acceptance. On the other hand, normative legitimacy examines whether the constitution is based on justifiable principles and whether it might be considered as legally binding. The constitutional process in 1989 - aimed at establishing a democratic transition – took place within round-table discussions of the representatives of the old system and the strengthened opposition. As a result of the radical changes, the democratic Constitution was established in Hungary and the multi-party system also developed. The outcome of the discussions was the general supervision of the Constitution. Formally, there was only an amendment to the Constitution in 1989; however, as regard its content, a completely new norm was established. Since the change of the political system in 1989, the idea of creating a new constitution emerges again and again in the Hungarian public life. In the course of the elections in 2010, a party alliance (in which both parties represented the same political line) reached the required two-thirds majority in the Parliament, and aimed at establishing a new constitution. The result of the constitutional process is a completely new constitution (both the form and the content of the previous constitution were changed). All things considered, it can be stated that the amendment to the Constitution in 1989 was accepted lawfully by the Parliament of the old system, i.e. the constitutional process was legal, and in a normative sense, a legitimate Constitution was created. In 2011, the Fundamental Law of Hungary (Hungarian: Magyarország Alaptörvénye) was adopted on the basis of the procedure determined by the Constitution in 1989, i.e. the constitutional process was legal, though; the present research paper highlights some elements of the constitutional process that might be criticized. At present, the legitimacy of the Fundamental Law of Hungary is controversial from both sociological and normative perspectives.